2011
DOI: 10.1371/journal.pone.0021107
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A and Retinoid Derivatives for Lung Cancer: A Systematic Review and Meta Analysis

Abstract: BackgroundDespite reported antiproliferative activity of vitamin A and its common use for cancer, there is no comprehensive synthesis of its safety and efficacy in lung cancers. To address this issue we conducted a systematic review of the safety and efficacy of vitamin A for the treatment and prevention of lung cancers.Methods and FindingsTwo independent reviewers searched six electronic databases from inception to July 2009 for clinical, observational, and preclinical evidence pertaining to the safety and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 85 publications
(129 reference statements)
2
46
0
1
Order By: Relevance
“…Fig. 1 showed the anti-angiogenic activity of each treatment where retinol palmitate(Positive Control) showed the highest activity followed by Pure Lumboy Extract (Treatment 2), and Pure Alugbati Extract (Treatment 1).This anti-angiogenic capacity of retinol palmitate was already reported in the studies of Fritz, et al, (2011) andNagpal &Chandraratna (1996). ANOVA revealed that the number of new-formed blood vessel branches among treatments, a 23.806 F-computed value and .000 probability value was attained.…”
Section: Statistical Treatmentsupporting
confidence: 69%
“…Fig. 1 showed the anti-angiogenic activity of each treatment where retinol palmitate(Positive Control) showed the highest activity followed by Pure Lumboy Extract (Treatment 2), and Pure Alugbati Extract (Treatment 1).This anti-angiogenic capacity of retinol palmitate was already reported in the studies of Fritz, et al, (2011) andNagpal &Chandraratna (1996). ANOVA revealed that the number of new-formed blood vessel branches among treatments, a 23.806 F-computed value and .000 probability value was attained.…”
Section: Statistical Treatmentsupporting
confidence: 69%
“…33,34 Retinol and its derivatives are thought capable of reducing oxidative stress and the risk of carcinogenesis. 35 However, considering the diversity of retinol's cellular activities (including cellular growth, differentiation, proliferation and apoptosis), the lack of convincing inverse associations for other carotenoids or vitamins and the remaining inverse association when adjusting for ROM, it is possible that the association between retinol and CRC is not due to its role as an antioxidant. 4,35 The association between retinol and colon cancer attenuated after exclusion of the case-control sets with a follow-up below 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, considering the diversity of retinol's cellular activities (including cellular growth, differentiation, proliferation and apoptosis), the lack of convincing inverse associations for other carotenoids or vitamins and the remaining inverse association when adjusting for ROM, it is possible that the association between retinol and CRC is not due to its role as an antioxidant. 4,35 The association between retinol and colon cancer attenuated after exclusion of the case-control sets with a follow-up below 2 years. This likely indicates a certain degree of reverse causality, possibly caused by the oxidative stress induced by the subclinical cancer as was suggested in the association between ROM and CRC previously within EPIC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the importance of RA is exemplified by its strong cellular differentiation-inducing capability and its utility in the therapy of acute promyelocytic leukemia. [8][9][10] RA also shows anti-proliferative activities against melanoma, 11) prostate cancer, 12,13) lung cancer, 14,15) and breast cancer, 16,17) but not against refractory cancers. None-the less, it is not known whether other forms of vitamin A, such as retinol and REs, in particular retinyl palmitate (RP), exhibit anti-cancer effects.…”
Section: -7)mentioning
confidence: 99%